Implementing Multicultural Education in Early Childhood: A Case Study of Abdullah School, Aligarh, India - Munastiwi, Erni; Muqowim, Muqowim (MyResearch ID Publishing, 2024)
Purpose – This study examines the implementation of multicultural education in early childhood settings in India, with a particular focus on Abdullah School in Aligarh, which serves a culturally and religiously diverse student body. It aims to address gaps in existing research by exploring how multicultural values are conceptualized and implemented, and their impact on students during early childhood, a critical developmental phase. Methods/Design/Approach – This qualitative case study utilized classroom observations, semi-structured interviews with school staff, and document analysis. The sample included the school’s principal, teachers, and students. Thematic analysis was employed to examine multicultural education practices, categorizing data into school policies and classroom activities that promote multicultural values. Findings – The study found that Abdullah School's approach to multicultural education is deeply rooted in principles of inclusivity, respect for diversity, and gender equality. The school integrates these values through tailored curricula for students of different religious backgrounds and promotes cooperation and tolerance through extracurricular activities. While effective, challenges related to infrastructure and societal biases were noted. Originality/Value – This study provides a rare analysis of multicultural education in early childhood settings in India, offering insights into the effectiveness of implementing multicultural values at a formative age. It highlights the unique socio-cultural context of India and offers practical models for fostering inclusivity and social harmony in diverse societies. Practical Implications – The findings suggest that schools with diverse populations can adopt dual-track curricula and extracurricular activities that emphasize respect for diversity. Policymakers should focus on providing infrastructure support and resources to sustain effective multicultural education. Keywords Multicultural education, early childhood, inclusivity, India, diversity Paper type Research paper